TEMPORAL VIDEO COMPRESSION USING MODE FACTOR AND POLYNOMIAL FITTING ON WAVELET COEFFICIENTS - Devi, TN; Lim , WK; Wan, WN; Tan, YF; Teng, HT; Chang, YF (2009)
The core idea of this study is to build an algorithm that functions to compress video sequences. The mode value at every pixel along the temporal direction is calculated. If the frequency of the mode value satisfies a predetermined frequency, then the intensity values for entire entries at that particular pixel position will be changed to the mode value. The wavelet techniques will be applied to the pixels that do not satisfy the predetermined frequency and followed by a polynomial fitting method. For the purpose of compression, only the polynomial coefficients for pixels that do not satisfy the predetermined frequency, the mode values for pixels that satisfy the predetermined frequency and the corresponding pixel positions will be stored. To decompress, wavelet coefficients are estimated by the respective polynomials. The intensity values at the intended pixel position are obtained by inverse wavelet transform for pixels that do not satisfy the predetermined frequency. On the other hand, the stored mode values will be used to represent the intensity values throughout the time interval. This method portrays a prospect to achieve an acceptable decompressed video quality and compression ratio.